2017
DOI: 10.4269/ajtmh.16-0487
|View full text |Cite
|
Sign up to set email alerts
|

Mass Azithromycin and Malaria Parasitemia in Niger: Results from a Community-Randomized Trial

Abstract: Abstract.Studies designed to determine the effects of mass administration of azithromycin on trachoma have suggested that mass azithromycin distributions may also reduce the prevalence of malaria. These studies have typically examined the impact of a small number of treatments over short durations. In this prespecified substudy of a cluster-randomized trial for trachoma, we compared malaria parasitemia prevalence in 24 communities in Niger randomized to receive either annual or biannual mass azithromycin distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Azithromycin has also been shown to prevent malaria infections, although its efficacy appears to be inferior to that of doxycycline [2, 3]. Malaria outcomes have been measured during studies of mass azithromycin distributions for trachoma, with reductions in malaria parasitemia observed in some studies but not in others [9, 13, 23, 24]. The present study improved upon previous studies of mass azithromycin distribution in that it was placebo controlled and enforced strict masking procedures both in the field and by laboratory staff.…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin has also been shown to prevent malaria infections, although its efficacy appears to be inferior to that of doxycycline [2, 3]. Malaria outcomes have been measured during studies of mass azithromycin distributions for trachoma, with reductions in malaria parasitemia observed in some studies but not in others [9, 13, 23, 24]. The present study improved upon previous studies of mass azithromycin distribution in that it was placebo controlled and enforced strict masking procedures both in the field and by laboratory staff.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are consistent with previously-reported results from 24 different communities randomized to annual versus biannual mass azithromycin distribution over a 36-month period in the same study. 11 In these studies, samples were collected during the high transmission season. It is possible that multiple mass azithromycin distributions increase selection of azithromycin-resistant strains, although we were unable to assess this here.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, there was no significant difference in malaria prevalence or parasitemia during the high transmission season between three annual compared with six biannual mass azithromycin distributions in a different set of communities. 11 Here, we report 36-month malaria parasitemia outcomes from the same trial collected during the peak transmission season after 3 annual or 6 biannual azithromycin distributions in the same communities in which a decrease in parasitemia prevalence was previously noted during the low transmission season following two mass azithromycin distributions compared with a single mass azithromycin distribution.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Azithromycin has modest activity against malaria by targeting the plasmodial apicoplast. 7 , 8 Although studies of mass azithromycin distribution for trachoma control have yielded mixed results, 9 12 a study of biannual mass azithromycin distribution for child mortality demonstrated a significant decrease in malaria parasitemia in communities receiving azithromycin compared with those receiving placebo. 13 Any relationship between malaria and malnutrition could potentially be affected by distribution of azithromycin to children given the overall effect in a reduction in malaria parasitemia.…”
Section: Introductionmentioning
confidence: 99%